Eligibility for cardiac resynchronization therapy in patients hospitalized with heart failure. (25th June 2018) - Osmanska, Joanna; Hawkins, Nathaniel M.; Toma, Mustafa; Ignaszewski, Andrew; Virani, Sean A.
Abstract: Aims: Recent guidelines recommend cardiac resynchronization therapy (CRT) in mildly symptomatic heart failure (HF) but favour left bundle branch block (LBBB) morphology in patients with moderate QRS prolongation (120–150 ms). We defined how many patients hospitalized with HF fulfil these criteria. Methods and results: A single‐centre retrospective cohort study of 363 consecutive patients hospitalized with HF (438 admissions) was performed. Electronic imaging, electrocardiograms, and records were reviewed. Overall, 153 patients (42%) had left ventricular ejection fraction (LVEF) ≤ 35%, and 34% of patients had QRS prolongation. Eighty patients (22%) were potentially eligible with LVEF ≤ 35% and QRS ≥ 120 ms or existing CRT. The majority (68 of 80) had a Class I or IIa recommendation according to international guidelines (LBBB or non‐LBBB QRS ≥ 150 ms or right ventricular pacing). Only a minority (12 of 80) had moderate QRS prolongation of non‐LBBB morphology. One‐quarter ( n  = 22) of patients fulfilling criteria were ineligible for reasons including dementia, co‐morbidities, or palliative care. A further eight patients required optimization of medical therapy. CRT was therefore immediately indicated in 50 patients. Of these, 29 were implanted or had existing CRT systems. Twenty‐one of the 80 patients eligible for CRT were not identified or treated (6% of the total hospitalized cohort). Conclusions: Twenty‐two per cent of elderly real‐life patients hospitalized with HF fulfil LVEF and QRS criteria for CRT, most having a Class I or IIa indication. However, a large proportion is ineligible owing to co‐morbidities or requires medical optimization. Although uptake of CRT was reasonable, there remain opportunities for improvement.